MENINGKATKAN HASIL BELAJAR SEMES BOLA VOLI MELALUI MODIFIKASI PERMAINAN BOLA GANTUNG PADA SISWA KELAS XI SMA FRATER PALOPO - Kanisius Kuma Lewar; Suaib Nur; Rasyidah Jalil; Irsan Kahar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve volleyball learning outcomes through the modification of the hanging ball game for Grade XI students of SMA Frater Palopo. The hanging ball modification was implemented to address low student learning outcomes, increase motivation, and create an active and enjoyable learning environment. This research employed a Classroom Action Research (CAR) method consisting of two cycles, each including planning, implementation, observation, and reflection stages. The subjects of the study were 20 Grade XI students, consisting of 12 male and 8 female students. The results showed an improvement in learning mastery in the aspects of knowledge, skills, and attitudes after the implementation of the hanging ball modification. In Cycle I, mastery levels for knowledge, skills, and attitudes reached 48%, 60%, and 72%, respectively. In Cycle II, the mastery levels increased to 84% for knowledge, 96% for skills, and 100% for attitudes. The application of the hanging ball modification proved effective in improving student learning outcomes in volleyball learning, with significant improvements observed in each cycle, indicating enhanced learning results and active student participation.